2008
DOI: 10.1166/jnn.2008.sw14
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Based Diagnostics Applied to the Study of BN Nanotubes Synthesis

Abstract: The boron nitride nanotubes (BNNTs) synthesis, using CO2-laser vaporization of a BN target under nitrogen gas, is investigated by UV-laser induced fluorescence (LIF) of the vapor phase and UV-Rayleigh scattering (RS) of the gas-suspended nanoparticles. The LIF signal from B atoms is mainly detected in the 1.5 mm-thick region above the BN target. It originates from a boron-rich vapor region confined near the hot boron droplet formed at the target surface. Then, recombination between hot boron and N2 gas occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Boron gets then vaporized although the equilibrium vaporization temperature is far to be obtained at the surface of the target. The existence of the boron vapor state has recently been attested by in situ fluorescence measurements: the boron vapor has been detected in a few millimeter thick layer just above the target surface …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boron gets then vaporized although the equilibrium vaporization temperature is far to be obtained at the surface of the target. The existence of the boron vapor state has recently been attested by in situ fluorescence measurements: the boron vapor has been detected in a few millimeter thick layer just above the target surface …”
Section: Resultsmentioning
confidence: 99%
“…This growth remains active as long as the boron particle is liquid, that is as long as the temperature is above 2300 K, according to the B−N phase diagram (step III in Figure ). Referring to the CARS measurements of temperature gradient of the nitrogen gas described above, , the solidification of the boron particle arises in a zone of the reactor chamber where the cooling rate is between 100 and 200 K/ms. This means that the growth of the tubes is abruptly stopped and explains the relative short length of SW-BNNTs compared to their carbon analogs synthesized via a continuous CO 2 laser vaporization of a NiCo-graphite target .…”
Section: Resultsmentioning
confidence: 99%
“…However, in doing so, it requires a profound understanding of the growth mechanism of BNNT in every single method. Recently, computer simulation and in situ diagnostic tools to evaluate every critical factor from several research groups have initially provided some insight into growing process of BNNT [ 51 , 53 , 58 ]. On the other hand, the widespread availability of BNNT has triggered great interest in the development of BNNT applications.…”
Section: Discussionmentioning
confidence: 99%
“…From the analysis of boron nanoparticle enclosed by h-BN layer, it was found that oxygen impurities could restrain the formation of BNNT. In situ diagnostic methods developed by Cau et al using the UV-laser induced fluorescence (LIF) and UV–Rayleigh scattering (RS) indicate the existence of BN and BO species in the plume above heated h-BN target [ 51 ]. The results supported the root growth mechanism and confirm the inhibition of BNNT growth due to oxygen impurities in previous studies.…”
Section: Bnnt Synthesis Methodsmentioning
confidence: 99%
“…42,[90][91][92] This technique for the BNNTs growth was rst introduced by Golberg et al 93 As precursor, single crystal of cubic BN (target) was heated with the help of CO 2 laser up to 5000 K to obtain MWBNNTs. 93 Later on, h-BN was also used as precursor in this technique [94][95][96][97][98][99] and both SWBNNTs and MWBNNTs were successfully synthesized. It was found that fabrication of BNNTs via this technique can be achieved without catalysts.…”
Section: Bnnts Synthesis Methodsmentioning
confidence: 99%